Multidisciplinary approach with predictable esthetics: A case report - Alhanouf A. Albarrak; Hamad S. AlRumaih; Abdulkareem Al-Humaidan; Ahmad M. Al-Thobity; Faris A. Alshahrani (Saudi Dental Journal)
This case report explains an effective multidisciplinary approach used to improve the function, biology, and esthetic of a patient presented with an excessive gingival display, a spacing between anterior teeth, small size anterior teeth in maxilla and mandible. Also, unrestorable molars were noted with multiple carious lesions. The treatment combined crown lengthening, prosthetic dentistry using lithium disilicate crowns and minimally invasive implants placement approach. Keywords: Multidisciplinary dentistry, Esthetic dentistry, Crown lengthening, Excessive gingival display, Dental implant, High smile line